Effect of 100 KeV Ar+ ion beam irradiation on ZnO thin films – Influence of morphology vis-a-vis electrode/electrolyte interface and its impact on photoelectrochemical water splitting. (11th June 2021) - Asha, Kumari; Biswas, Neeraj Kumar; Saxena, Sakshi; Satsangi, Vibha Rani; Shrivastav, Rohit; Kant, Rama; Dass, Sahab
Abstract: The present study attempts quantitative determination of changes in the morphological surface features viz. fractal dimension, lower and upper cut off length scale through Power Spectral Density analysis prior to and after irradiation of 100 KeV Ar + ion beam at incidence angles of 0°, 40° and 60° on ZnO thin films. All the unirradiated and irradiated samples are subjected to photoelectrochemical characterization and a correlation between photoelectrochemical performance and morphological parameters is established. Sample irradiated at 40° angle at the fluence of 5 × 10 16 ions/cm 2 is found to possess maximum fractal dimension of 2.72, lower and upper cut off length scale of 3.16 nm and 63.00 nm respectively. This sample exhibits maximum photocurrent density of 3.19 mA/cm 2 and applied bias photon-to-current efficiency of 1.12% at 1.23 V/RHE. Hydrogen gas collected for duration of 1 h for the same sample was ~4.83 mLcm −2 . Graphical abstract: Image 1 Highlights: ZnO films irradiated with 100 KeV Ar + beam at 0°, 40° and 60° at various fluences. Morphological parameters calculated using PSD analysis from AFM images. Correlation between morphological and PEC parameters is developed.